Association of infection among intrauterine contraceptive device users in family planning clinics in Sudan - Alawad, Awad; Bashir, Mohammed Elkhair (International Journal of Health, 2014)
Background: Intrauterine contraceptive device (IUCD) is one of the most widely used methods of reversible birth control. Consequently, the existence and consequences of insertion, removal and associated infection have received little attentionObjective: To identify the type and to determine the incidence of infection associated with IUCD users through screening by culturing endocervical swabs.Methods: This is a descriptive, cross sectional, facility based study conducted in family planning clinics in Khartoum. This study was carried out on 35 ladies, attending the clinics during the period of study, using IUCD, presented for follow up, complaining or for removing the IUCD, who fulfilled the criteria of selection after obtaining an informed consent.Results: The incidence of positive culture swab among users was 65.0%. Among the study population, the age distribution was found to be varying between 24 and 39 years, taking a range of 4 years between groups of study population. Regarding complaint, vaginal discharge was found among 32 (91.4%) users, intermenstrual bleeding was present among 15 (42.9%) users, menorrhagia has been present in 11 (31.4%) users, abdominal discomfort was noticed among 6 (17.1%) users, and postcoital bleeding was present in 5 (14.3%) users. Result of swab culture shows that, 12 women (34%) of users culture of no growth, while 9 of them Staph.spp positive culture, there were 3 women (8.6%) users with culture result of E.coli, and 3 women (8.6%) users with culture result of candida albicans, there were 2 women (5.7%) users with culture result of coliform and other 2 women (5.7%) users with culture positive for trichomonas vaginalis.Conclusion: The study concluded that incidence of positive cultures among IUCD users was 65.0% and about two third of female in the family planning clinics had mild to moderate levels of infection. The most common isolated organisms among IUCD users in this study were Staph spp, E.coli and Candida .The study also showed high rate of removal of IUCD copper type and most of removal due to dyspareunia.